2021
DOI: 10.1002/jper.21-0439
|View full text |Cite
|
Sign up to set email alerts
|

Access to dental care and blood pressure profiles in adults with high socioeconomic status

Abstract: Background: Reduced access to dental care may increase cardiovascular risk; however, socioeconomic factors are believed to confound the associations. We hypothesized that the relation persists despite economic wellness and high education, with reduced access to dental care affecting cardiovascular risk at least in part through its effect on blood pressure (BP), possibly mediated by systemic inflammation. Methods:We first assessed the sociodemographic and clinical characteristics related to last dental visit ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…These findings provide the first evidence of the association between home oral hygiene habits and BP, and expand previous observational evidence on the association between periodontal health status and BP profile (Pietropaoli et al, 2018 ; Pietropaoli, Del Pinto, et al, 2020 ), while also adding to recent evidence linking oral health habits with cardiovascular health (Park et al, 2019 ; Del Pinto, Monaco, et al, 2021 ; Hwang et al, 2022 ). In fact, cross‐sectional evidence from the Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2010 showed that the adjusted prevalence of hypertension decreased as the frequency of toothbrushing increased, but the impact of toothbrushing modality was only assessed in combination with the use of other oral products (Choi et al, 2015 ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings provide the first evidence of the association between home oral hygiene habits and BP, and expand previous observational evidence on the association between periodontal health status and BP profile (Pietropaoli et al, 2018 ; Pietropaoli, Del Pinto, et al, 2020 ), while also adding to recent evidence linking oral health habits with cardiovascular health (Park et al, 2019 ; Del Pinto, Monaco, et al, 2021 ; Hwang et al, 2022 ). In fact, cross‐sectional evidence from the Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2010 showed that the adjusted prevalence of hypertension decreased as the frequency of toothbrushing increased, but the impact of toothbrushing modality was only assessed in combination with the use of other oral products (Choi et al, 2015 ).…”
Section: Discussionsupporting
confidence: 83%
“…More recently, a study has assessed the association of tooth brushing frequency with incident hypertension in middle-aged and older Korean adults, reporting a 15% reduced risk of the outcome among individuals who brushed their teeth at least three times/day, but the modality of brushing (electric/manual) was not assessed (Hwang et al, 2022). In parallel, an analysis of 2350 propensity-matched, highly educated, high-income adults from the National Health and Nutrition Examination Survey (NHANES) found that regular access to dental care impacts on BP profiles independent of socio-economic confounders, with reduced risk of high/ T A B L E 3 Crude results of interaction analysis between daily toothbrushing (≥ or <3 times/day) and toothbrush type (manual/electric) uncontrolled BP in association with attendance ≤6 months compared with attendance >6 months (Del Pinto, Monaco, et al, 2021). From a biological standpoint, nearly 7% of the effect of accessing dental care on BP was mediated by low-grade systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tooth loss has been debated as a potential marker of cerebral stroke. Some cross-sectional studies have addressed the fact that patients with a fewer number of teeth may be associated with increased risks of stroke or other systemic diseases [ 109 , 110 , 111 ]. On the other hand, if tooth loss is caused during the early years of life or is due to other factors such as caries or trauma, the patients might not have been affected by periodontal disease for the rest of their life [ 112 , 113 ].…”
Section: Relation Between Tooth Conditions and Strokementioning
confidence: 99%